Institute for Societal Leadership officially launched by Singapore Deputy Prime Minister Mr Tharman Shanmugaratnam at Societal Leadership Summit 2016 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2016)
The Institute for Societal Leadership (ISL) under the Singapore Management University (SMU) was today officially launched by distinguished Guest of Honour Mr Tharman Shanmugaratnam, Deputy Prime Minister (DPM) and Coordinating Minister for Economic and Social Policies of Singapore, during the Societal Leadership Summit 2016. DPM Tharman also delivered a keynote address on societal leadership. ISL is the first and only institution in Asia that focuses on societal leadership. The Institute was formed to advance Societal Leadership in Southeast Asia and beyond. It is anchored on SMU’s foundation of academic rigour and aims to achieve a greater applied understanding of societal leadership. ISL seeks to be a thought leader in societal leadership for the betterment of society. It provides a convening and collaborative platform for societal leaders, and is a capacity builder to inspire and develop current and emerging societal leaders.